2010
DOI: 10.1017/s0144686x10000577
|View full text |Cite
|
Sign up to set email alerts
|

Leisure activities and retirement: do structures of inequality change in old age?

Abstract: In this paper, relationships between old age, retirement and social inequalities, as marked by participation in leisure activities, are examined. Two issues are tackled : first, whether old age and particularly the transition into retirement have an effect on participation in three selected activities ; and second, whether the social inequalities underlying these activities change with older age and retirement. The empirical investigation uses data from the first two waves of the English Longitudinal Study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 34 publications
0
60
0
7
Order By: Relevance
“…The transition to retirement involves both gains and losses and leisure can play an important role in a person's adjustment (Carpenter and Patterson 2004;Earl, Gerrans, and Halim 2015;Nimrod 2007). However, research suggests that retirement can have a negative impact on leisure particularly if retirement was prompted by illness or if it is accompanied by a decline in financial resources (Scherger, Nazroo, and Higgs 2011).…”
Section: Leisure and Retirementmentioning
confidence: 99%
“…The transition to retirement involves both gains and losses and leisure can play an important role in a person's adjustment (Carpenter and Patterson 2004;Earl, Gerrans, and Halim 2015;Nimrod 2007). However, research suggests that retirement can have a negative impact on leisure particularly if retirement was prompted by illness or if it is accompanied by a decline in financial resources (Scherger, Nazroo, and Higgs 2011).…”
Section: Leisure and Retirementmentioning
confidence: 99%
“…Further, it has been shown that entering retirement does not have a strong effect on the level of leisure participation (see, e.g. Scherger et al 2011). However, with the growing role of the Internet as an everyday activity, as well as its potential incentive for other leisure activities (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, research within the UK consistently highlights the diversity of fortune and experience within the Baby Boomer generation, and the extent to which people's experience within later life is shaped by factors of social class, income inequality, employment, (ill) health, gender, ethnicity, and family support networks as much as, if not more than, by their generational location (see Leach ; Phillipson ; Pilcher ). Indeed, as Scherger et al () suggest, in their study of leisure activities and inequality in retirement, this challenges the idea that the ‘new old age’ has become a reality for most people:
The Third Age as imagined by Laslett (1987, 1996/1989), a time of new activities and self‐development, has not become reality, notwithstanding that the prospects of a continuing active lifestyle after retirement seem to be good for most retirees, and that some privileged groups come close to Laslett's vision. (Scherger et al : 167)
…”
Section: Discussion: the Cross‐national Diffusion Of The Baby Boomer mentioning
confidence: 99%